Protective Effects of Eicosapentaenoic Acid Plus Hydroxytyrosol Supplementation Against White Adipose Tissue Abnormalities in Mice Fed a High-Fat Diet - Paola Illesca; Rodrigo Valenzuela; Alejandra Espinosa; Francisca Echeverría; Sandra Soto-Alarcon; Cristian Campos; Alicia Rodriguez; Romina Vargas; Thea Magrone; Luis A. Videla (Molecules, 2020)
Objective: Obesity induced by high-fat diet (HFD) elicits white adipose tissue dysfunction. In this study, we have hypothesized that the metabolic modulator eicosapentaenoic acid (EPA) combined with the antioxidant hydroxytyrosol (HT) attenuates HFD-induced white adipose tissue (WAT) alterations. Methods: C57BL/6J mice were administered with a HFD (60% fat, 20% protein, 20% carbohydrates) or control diet (CD; 10% fat, 20% protein, 70% carbohydrates), with or without EPA (50 mg/kg/day), HT (5 mg/kg/day), or both for 12 weeks. Determinations in WAT include morphological parameters, EPA and docosahexaenoic acid content in phospholipids (gas chromatography), lipogenesis, oxidative stress (OS) and inflammation markers, and gene expression and activities of transcription factors, such as sterol regulatory element-binding protein-1c (SREBP-1c), peroxisome proliferator-activated receptor-gamma (PPAR-γ), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) (p65 subunit) and nuclear factor erythroid 2-related factor 2 (Nrf2) (quantitative polymerase chain reaction and enzyme linked immunosorbent assay). Results: HFD led to WAT hypertrophy in relation to PPAR-γ downregulation. WAT metabolic dysfunction was characterized by upregulation of lipogenic SREBP-1c system, mitochondrial energy metabolism depression, loss of the antioxidant Nrf2 signaling with OS enhancement, n-3 long-chain polyunsaturated fatty acids depletion and activation of the pro-inflammatory NF-κB system. EPA and HT co-supplementation diminished HFD-dependent effects additively, reaching values close or similar to controls. Conclusion: Data presented strengthen the importance of combined protocols such as EPA plus HT to attenuate metabolic-inflammatory states triggered by obesity.